Spectroscopy of B-type emission-line stars with compact dusty envelopes: HD 85567, Hen 3-140, and Hen 3-1398 - Miroshnichenko, A. S. (2001)
We report the results of our spectroscopic observations (3600-5900 Å, R ≃ 16000 and 5750-8750 Å, R ≃ 11000) of three southern emission-line B-type stars associated with IRAS sources, HD 85567, Hen 3-140, and Hen 3-1398, whose nature and evolutionary state are not well-established yet. We also obtained new multicolour photometry of HD 85567 (UBV(RI)cJHKL) and (JHKLM). A large near-IR excess is found in Hen 3-140 for the first time. All three objects show double-peaked Fe II lines in emission. The Balmer emission lines are double-peaked in HD 85567 and Hen 3-140, while the He I lines are found in absorption. Hen 3-1398 displays triple-peaked Balmer lines as well as single-peaked He I and He II lines in emission. Fundamental parameters of the stars are estimated on the basis of both photometric and spectroscopic data. The whole set of their properties resemble that of a recently defined group of Be stars with warm dust (Sheikina et al. 2000).